Pola Komunikasi Urban Care Community pada Masyarakat Marginal Surabaya - Dian Maulana Chandra; Pardianto Pardianto (Jurnal Ilmu Komunikasi, 2019)
Marginalization still occurs in some communities in the city of Surabaya. One of them is the people in the Kali Jagir village of Surabaya. Urban Care Community is a non-governmental organization (NGO) that fosters marginalized communities in Stren Kali Jagir, Wonokromo, Surabaya City. This article discusses how the Urban Care Community process and communication patterns among marginalized communities in the Kali Jagir Stren. The purpose of this study was to determine the patterns and processes of Urban Care Community communication in empowering marginalized communities in Stren Kali Jagir. This study uses a qualitative descriptive research method. The result of this research is the communication process carried out by the Urban Care Community with marginalized communities in the Kali Jagir Stren using interpersonal communication processes, group communication, and social media communication to make it more efficient. Meanwhile, the communication pattern with marginalized communities in Stren Kali Jagir uses a secondary communication pattern